Circulating Tumor DNA Analyses Predict Disease Recurrence in Non-Muscle-Invasive Bladder Cancer - Zhang, Jinghua; Dai, Daofeng; Tian, Junqiang; Li, Lifeng; Bai, Jing; Xu, Yaping; Wang, Zhiping; Tang, Aifa (Frontiers in Oncology, 2021)
Circulating tumor DNA (ctDNA) can be a prognostic biomarker for non-muscle-invasive bladder cancer (NMIBC); however, targeted sequencing has not been performed to detect ctDNA in NMIBC. We applied targeted sequencing based on an 861-gene panel to determine mutations in tumor tissue DNA and plasma ctDNA in 82 NMIBC patients receiving transurethral resection (TUR) of bladder followed by chemotherapy. We detected 476 and 165 somatic variants in tumor DNA from 82 NMIBC patients (100%) and ctDNA from 54 patients (65.85%), respectively. Patients with high heterogeneity in tumor DNA had a significantly shorter disease-free survival than those with low heterogeneity. Tumor-derived alterations were detectable in plasma of 43 patients (52.44%). The concordance of somatic variants between tumor DNA and plasma ctDNA were higher in patients with T1 stage (p < 0.0001) and tumor size ≥ 3 cm (p = 0.0002). Molecular tumor burden index (mTBI) in ctDNA positively correlated with larger tumor size (p = 0.0020). A higher mTBI was an independent predictor of recurrence after TUR of bladder followed by chemotherapy. Analysis of ctDNA based on targeted sequencing is a promising approach to predict disease recurrence for NMIBC patients receiving TUR of bladder followed by chemotherapy.